Critical and pedagogical leadership: teaching and organic intellectuality - Robles Barrantes, Ariel; Arguedas Zúñiga, Roberto (Innovaciones Educativas, 2020)
This academic essay aims to promote the exercise of critical and pedagogical leadership. It is understood that it implies creating participative processes that are dialogic, emancipating, contextualized and transforming, where teachers can contribute as organic intellectuals by generating answers for the needs of those are more vulnerable and who find themselves directly involved in the educational context. The present essay’s methodological approach has its origins in studying what it means to be a teacher, what is leadership, and pedagogical leadership to build the concept of critical pedagogical leadership. Also, it examines the competencies that combine the implications of teaching and its scope in pedagogy while questioning the teaching role under the focus of organic intellectuality. This teaching vindication implies going beyond the impacts of the prevailing economic model, the role of the State in the educational context, and the systematic demands of educational models that condition the role and professional training in favor of a merely technical perspective. In conclusion, understanding the context marked by neoliberalism in which Latin American teachers’ work unfolds makes it possible to perceive the reasons for promoting their leadership as a social transformation mechanism, but not from the official discourse and nor driven by an educational system. Critical pedagogical leadership must be built from a pedagogical conception and a collective effort, beyond individual practices, a process in which the organic intellectuality is found as an instrument to achieve the goal.